Assessment of the Success of the Independent Campus Independent Learning Program Through a Web-Based Integration System at the Participating University - Henny Setiani; Yayat Ruhiat; Aan Hendrayana (Postgraduate, University of Mataram, 2024)
This study explores the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program in private universities in Banten Province, Indonesia, emphasizing the importance of a well-structured curriculum for effective learning outcomes. The policy enables students to engage in various activities outside their majors, enhancing both technical and soft skills essential for workforce readiness. Despite its positive reception, challenges in the assessment conversion process have been identified, particularly the lack of involvement from study program leaders and course lecturers in evaluating student performance. This study employs the R&D method using the ADDIE model to develop a web-based integration system aimed at streamlining and improving the evaluation of student achievements in the MBKM program. The findings indicate that this system enhances monitoring, transparency, and accountability in assessment, fostering better collaboration among lecturers, students, and partner institutions. Moreover, the web-based system alleviates administrative burdens, allowing lecturers to focus on enriching student learning experiences. This research underscores the necessity for continuous evaluation of the MBKM program to align competencies with academic curricula, ultimately contributing to the quality of higher education and the successful integration of students into the workforce. Recommendations for further development of the integration system and enhanced training for lecturers are provided to optimize its impact on educational outcomes.